Soy consumption and serum uric acid levels: A systematic review and meta-analysis - Duan, Ying; Qi, Qi; Liu, Zihao; Zhang, Min; Liu, Huaqing (Frontiers in Nutrition, 2022)
Background Soy consumption has health benefits, but the relationship between soy and uric acid remains uncertain. This meta-analysis and systematic review evaluated effects of soy intake on plasma uric acid. Methods PubMed, Embase, CNKI, and the Cochrane Library were searched for studies evaluating the effects of soy, soy products, soy protein, and soy isoflavones on uric acid levels. The primary outcome was serum or plasma uric acid concentration. Study quality was evaluated by the Cochrane Collaboration and SYRCLE risk-of-bias tools. Results Seventeen studies were included. Qualitative analysis of three human clinical studies of acute effects revealed that soy consumption increased serum uric acid concentration; however, soy-derived products, including tofu, bean curd cake, and dried bean curd sticks, had no significant effect on serum uric acid. Meta-analysis of five long-term human studies (10 data sets) revealed that soy protein and soy isoflavones had no significant effects on uric acid levels (weighted mean difference [WMD] = −2.11; 95% confidence interval [CI]: −8.78, 4.55; p = 0.53). However, most epidemiological data revealed that soy intake is inversely associated with uric acid levels. Meta-analysis of nine animal trials (29 data sets) revealed that soy protein and soy isoflavones significantly reduced serum uric acid concentrations (vs. controls; MD = −38.02; 95% CI: −50.60, −25.44; p < 0.001). Conclusion Soy and its products have different effects on serum uric acid. Soy products like tofu, bean curd cake, and dried bean curd sticks could be high-quality protein sources for individuals with hyperuricemia or gout. It can be beneficial to nutritionists and health-care decision makers reconsider their conceptions about the relationship between soy and uric acid levels according to latest and further scientific study results.